2007
DOI: 10.1007/s10616-007-9049-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: recently discovered key regulators of proliferation and apoptosis in animal cells

Abstract: The relatively recent discovery of miRNAs has added a completely new dimension to the study of the regulation of gene expression. The mechanism of action of miRNAs, the conservation between diverse species and the fact that each miRNA can regulate a number of targets and phenotypes clearly indicates the importance of these molecules. In this review the current state of knowledge relating to miRNA expression and gene regulation is presented, outlining the key morphological and biochemical features controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 113 publications
3
48
0
Order By: Relevance
“…Recent works demonstrate that HIF-1α may also serve as a transcription factor for the expression of noncoding genes, including microRNAs (miRs) (15). miRs are now known to play a key role in cell proliferation (16). We observed that ischemic wounds have a higher abundance of the HIF-1α-dependent miR-210 (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Recent works demonstrate that HIF-1α may also serve as a transcription factor for the expression of noncoding genes, including microRNAs (miRs) (15). miRs are now known to play a key role in cell proliferation (16). We observed that ischemic wounds have a higher abundance of the HIF-1α-dependent miR-210 (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…For example, the miR-34a, b, c, and miR-214 were observed to promote apoptosis by increasing the expression of Caspases, P21, P53, and Bax (Corney et al 2007, Gammell 2007, Zenz et al 2009). miR-210 and miR-155 repressed apoptosis by decreasing the expression of pro-apoptotic Caspases (Wang & Lee 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One of the hottest new topics in metabolic regulation is the control of mRNA expression by microRNA (miRNA). miRNAs are small non-coding transcripts (19-25 nucleotides long) that bind to target mRNAs; a perfect sequence match between a miRNA species and its target typically directs the mRNA into degradation pathways, whereas an imperfect match leads to translational inhibition via storage in cytoplasmic P-bodies [30] . Regulation by miRNA control over mRNA translation is now known to be particularly important in the regulation of development, and aberrant miRNA expression patterns have been linked with multiple diseases [31] .…”
Section: Global Metabolic Arrestmentioning
confidence: 99%